2014
DOI: 10.1007/s00520-014-2422-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding narrative effects in physical activity promotion: the influence of breast cancer survivor testimony on exercise beliefs, self-efficacy, and intention in breast cancer patients

Abstract: The results suggest that narratives may be more effective in improving perceived physical abilities and involvement in physical activity, whereas informational messages seem to be more appropriate to convey the benefits and the absence of risks related to physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Thus, the addition of a narrative to AVGs could promote strong intrinsic motivation by inclining attention to the game, promoting instant enjoyment for a new type of game, triggering exploration of the game environment 65 , and absorbing players in an immersive fictional world 66 , thereby stimulating a more physically-active movement 10 . Falzon and colleagues 67 using a survey instrument showed that a narrative might be an effective delivery method for improving intention and positive beliefs regarding physical activity in sedentary, middle-aged women with breast cancer undergoing chemotherapy. Taken together, our results and those from other studies suggest that a narrative is an effective motivational strategy for increasing physical activity and promoting physical activity behavior, regardless of age and health status.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the addition of a narrative to AVGs could promote strong intrinsic motivation by inclining attention to the game, promoting instant enjoyment for a new type of game, triggering exploration of the game environment 65 , and absorbing players in an immersive fictional world 66 , thereby stimulating a more physically-active movement 10 . Falzon and colleagues 67 using a survey instrument showed that a narrative might be an effective delivery method for improving intention and positive beliefs regarding physical activity in sedentary, middle-aged women with breast cancer undergoing chemotherapy. Taken together, our results and those from other studies suggest that a narrative is an effective motivational strategy for increasing physical activity and promoting physical activity behavior, regardless of age and health status.…”
Section: Discussionmentioning
confidence: 99%
“…One study identified how this relied on the participants' ability to believe and trust in the message from the other members of the group. One of the studies [31] measured "source trust" (the belief and trust in the person giving the message). This quality was higher in the storytelling group compared to comparison group (T = −10.61, p < 0.001).…”
Section: Sub-theme (D) Legitimising or Rationalising The Experiences mentioning
confidence: 99%
“…Institutional norms can also govern what stories can be told and how and when these should be communicated. All this recognized, research has shown that narratives Disability sport and activist identities 31 contribute more positively to promoting different identities, producing greater affective and motivational reactions, and changing health behaviors than cognitive orientated informational messages (e.g., Falzon, Radel, Cantor & d'Arripe-Longueville, 2015;Nelson, 2001). Given this, amplifying stories of activism could expand people's menu of narrative resources to choose from, thereby potentially opening up possible selves and enabling a highly multifaceted identity.…”
Section: Closing Thoughtsmentioning
confidence: 99%